IMPACT OF NURSERY USING DIFFERENT PHYSICAL FILTRATION SYSTEM ON HEMOLYMPH GLUCOSE LEVEL AND SURVIVAL RATE OF SPINY LOBSTER JUVENILE Panulirus homarus - Ega Aditya Prama; Eddy Supriyono; Kukuh Nirmala; Kukuh Adiyana (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2017)
The problems in culture of early juvenile phase of spiny lobster Panulirus homarus is low survival rate of the seed. One of strategies to improve production is using filtration system during nursery of spiny lobster. The aim of this study to evaluate differentation of physical filtration system on responsse stress and survival rate of juvenile P. homarus. Experimental design of this study consisted of four treatments and two replications. The treatments were using flow through system without protein skimmer and filter (K), filtration system with protein skimmer (SK), filtration system with top filter (F) and filtration system with combinations of protein skimmer and top filter (SKF). P. homarus with initial weight 0.18+0.01 g were cultured for 60 days with density 250 lobster/tank. During maintenance, P. homarus were fed trash fish with feeding rate 20% of body weight. Parameters of glucose hemolymph were evaluated to determine stress response. Stress response was determined at day 0, 6, 20 and 60. Parameters of survival rate were determined at the end of experiment. The result showed that the treatment of filtration system with combination of protein skimmer and top filter (SKF) decreased stress responsse by decreasing glucose hemolymph of juvenile P. homarus during maintenance. Survival rate also higher (P<0.05) in treatment SKF (33.2%) than other treatments. It is concluded that SKF was the best physical filtration system for juvenile period of spiny lobster P. homarus  Keywords: filtration system, glucose hemolymph, spiny lobster, survival rate